Actitudes de Los Padres De Familia y Estudiantes Adolescentes Frente al Fracaso Escolar (2015)
This research evaluates attitudes parents 3 and 3 teenage students against school failure Cycle 3 A, the college town of Kennedy Eighth night shift. To make research took into account the responses of the interviewees of the attitude that generates academic failure, compiling the required information through a semi-structured interview guide. On the other side are set as a general category attitudes and subcategories as cognitive, affective and behavioral component. It was evident that both parents and students, there are gaps against treating topic saying not know why school failure occurs, or know what solutions give to decrease and to help their children or help them students decrease poor school performance.